Review of Energy Efficiency Evaluation Indexes Related to Data Center Cooling Systems - Wang Bo; Guo Yanhua; Shao Shuangquan; Tu Qiu; Li Qianli (Zhileng xuebao)
Cooling systems consume a significant amount of energy to ensure the reliable operation of data centers. To help data centers achieve carbon neutrality and fully utilize the energy-saving potential of the cooling system, the energy efficiency of data center cooling systems should be evaluated. Many evaluation indexes of these cooling systems are used in the industry. In this study, the energy efficiency evaluation indexes of data center cooling systems presented in the current standards and literature are investigated, and the related indexes are explored as follows: electric energy utilization efficiency and related indexes of derivative cooling systems, performance indexes of data center cooling systems, and performance indexes of data center cold source equipment. The calculation methods and components of different indexes are introduced, and the advantages and disadvantages of each index are analyzed. Comparative experiments reveal that the power usage effectiveness(PUE) and related derivative indexes of the cooling systems cannot accurately reflect the technical level of the operation and maintenance of the data center. For the energy efficiency evaluation of the actual data center cooling systems, the annual general coefficient of performance(GCOPA) is applicable. For the annual operation index of chillers in Chinese data centers, the annual coefficient of performance(ACOP) is applicable.